Tự học viết tiếng Nhật căn bản - Nguyễn Văn Phước (Trẻ, 2002)
Beginner-level students wishing to read Japanese need to learn hiragana, the most basic of three Japanese scripts, used for writing words of native origin. Kodansha's Hiragana Workbook is an all-new, streamlined workbook designed precisely for such students. It introduces all aspects of the script-reading, writing, and pronunciation--in a fun, accessible format, packed with illustrations and exercises.